2007
DOI: 10.1055/s-2007-991128
|View full text |Cite
|
Sign up to set email alerts
|

Movement Disorders in Pregnancy

Abstract: Movement disorders are not commonly seen during pregnancy. As a result, there are few studies on whether disease manifestations are affected by the hormonal changes that occur during pregnancy or on the teratogenicity of commonly used medications for movement disorders on the developing fetus. This article discusses movement disorders that are seen only during pregnancy (chorea gravidarum) or that may present during pregnancy (restless legs syndrome), the effect that pregnancy has on symptoms and treatment (in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 74 publications
0
24
0
Order By: Relevance
“…Approximately one third of patients go into remission after delivery, and another subset are essentially free of the illness after delivery. 3,4 In its most severe form, CG can also cause hyperthermia, rhabdomyolysis, myoglobinuria, and eventually death. 5 CG is usually self-limited condition and manageable non-pharmacologically.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately one third of patients go into remission after delivery, and another subset are essentially free of the illness after delivery. 3,4 In its most severe form, CG can also cause hyperthermia, rhabdomyolysis, myoglobinuria, and eventually death. 5 CG is usually self-limited condition and manageable non-pharmacologically.…”
Section: Discussionmentioning
confidence: 99%
“…DYT1 dystonia typically begins during childhood and persists throughout life thus having the potential to cause difficulty during pregnancy 1. As there is currently no curative treatment, most patients are managed with lifelong medication and few by deep brain stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Pregnancy during PD is a rare phenomenon. Although studies have reported that there is an increased rate of both motor and non-motor symptoms during pregnancy in spite of the higher level of estrogens, however; it is rarely significant enough to impact the women's overall level of functioning [30]. Shulman in a case study reported a 33-year old woman with PD who experienced a significant worsening of PD symptoms during her pregnancy.…”
Section: Biochemical Factorsmentioning
confidence: 99%